Catalytic and mechanistic studies of a highly active and E-selective Co(ii) PNNH pincer catalyst system for transfer-semihydrogenation of internal alkynes. Issue 4 (20th January 2022) - Decker, David; Wei, Zhihong; Rabeah, Jabor; Drexler, Hans-Joachim; Brückner, Angelika; Jiao, Haijun; Beweries, Torsten
Abstract : A Co(II) PNN H pincer catalyst system for the highly E -selective transfer-semihydrogenation of internal alkynes using ammonia borane and MeOH as the hydrogen source is described. The reaction is proposed to occur via the Co(ii ) oxidation state. Abstract : Herein we report the application of a Co(ii ) PNN H pincer catalyst system (PNN H = 2-(5-( t -butyl)-1 H -pyrazol-3-yl)-6-(dialkylphosphinomethyl)pyridine) for the highly E -selective transfer semihydrogenation of internal diaryl alkynes using methanol and ammonia borane as hydrogen donors. The catalyst system is highly active (short reaction times, low Co concentration) and operates at very mild conditions (low temperature and transfer hydrogenation conditions). Spectroscopic and computational studies suggest that catalysis occurs via the Co(ii ) oxidation state, most likely with a Co(ii ) hydride as the key intermediate. Computational analysis of the reaction mechanism further rationalises the selective formation of E -alkenes and the absence of overreduction to produce alkanes.